Direct detection with an optimal transfer function: toward the electrical spectral efficiency of coherent homodyne detection - Xingfeng Li; Jingchi Li; Xiong Ni; Hudi Liu; Qunbi Zhuge; Haoshuo Chen; William Shieh; Yikai Su (Opto-Electronic Science)
Complex-valued double-sideband direct detection (DD) can reconstruct the optical field and achieve a high electrical spectral efficiency (ESE) comparable to that of a coherent homodyne receiver, and DD does not require a costly local oscillator laser. However, a fundamental question remains if there is an optimal DD receiver structure with the simplest design to approach the performance of the coherent homodyne detection. This study derives the optimal DD receiver structure with an optimal transfer function to recover a quadrature amplitude modulation (QAM) signal with a near-zero guard band at the central frequency of the signal. We derive the theoretical ESE limit for various detection schemes by invoking Shannon’s formula. Our proposed scheme is closest to coherent homodyne detection in terms of the theoretical ESE limit. By leveraging a WaveShaper to construct the optimal transfer function, we conduct a proof-of-concept experiment to transmit a net 228.85-Gb/s 64-QAM signal over an 80-km single-mode fiber with a net ESE of 8.76 b/s/Hz. To the best of our knowledge, this study reports the highest net ESE per polarization per wavelength for DD transmission beyond 40-km single-mode fiber. For a comprehensive metric, denoted as 2ESE×Reach, we achieve the highest 2ESE×Reach per polarization per wavelength for DD transmission.